Hur djurskyddet skiljer sig mellan odlad och vildfångad fisk vid avlivning : svensk lagstiftning, ASC, MSC & KRAV - Axelsson, Caroline (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
I have investigated what the Swedish legislation for farmed and wild caught fish have in common and what the differences are, also if the private standards ASC, MSC and KRAV have any additional rules that imply animal welfare in the slaughter/killing-process. The results show that there is only one similarity in the Swedish legislation between farmed and wild caught fish in the slaughter/killing-process. They are both represented in one single paragraph about animal abuse. The rest are differences.